Forecasting Implementation, Adoption and Evaluation Challenges For an Electronic Game-Based Antimicrobial Stewardship Intervention: Results of a Codesign Workshop with Experts (Preprint) - Castro-Sánchez,E; Sood,A; Rawson,TM; Firth,J; Holmes,AH (Journal of Medical Internet Research, 2019)
Background:Serious games have been proposed to address the lack of engagement and sustainability traditionally affecting interventions aiming to improve optimal antibiotic use among hospital prescribers.Objectives:To forecast gaps in implementation, adoption and evaluation of game-based interventions, and co-design solutions with antimicrobial clinicians and digital and behavioural researchers. Methods: A co-development workshop with clinicians and academics in serious games, antimicrobials and behavioural sciences was organised to open an international summit on serious games for health in London (United Kingdom), in March 2018. The workshop was announced on social media and online platforms. On the day, attendees were asked to work in small groups provided with a laptop/tablet with the latest version of ‘On call: Antibiotics. A workshop leader guided open group discussions around implementation, adoption and evaluation threats and potential solutions. Workshop summary notes were collated by an observer.Results: 29 participants attended the workshop. Anticipated challenges to resolve reflected implementation threats such as an inadequate organisational arrangement to scale and sustain the use of the game, requiring sufficient technical and educational support and a streamlined feedback mechanism that made best use of data arriving from the game; adoption threats, particularly collective perceptions that a game would be a ludic rather than professional tool, and demanding efforts to integrate all available educational solutions so none is seen as inferior; and evaluation threats due to the need to combine game metrics with organisational indicators such as antibiotic use, which may be difficult to enable.Conclusions:As with other technology-based interventions, organisations interested in deploying game-based solutions should carefully plan how to engage and support clinicians in their use, and how best integrate the game and game outputs onto existing workflo